SEMANTIC CHARACTERISTICS OF PHRASEOLOGICAL TOPONYMS - Pulatova Ra’no Ravshanovna (Western European Studies, 2025)
This aricle explores the semantic characteristics of phraseological toponyms—place names that carry figurative or idiomatic meanings beyond their literal geographic references. Phraseological toponyms often emerge from cultural narratives, historical events, or folk expressions, and they serve as linguistic markers of collective memory, identity, and worldview. The study examines how these toponyms function within language as culturally loaded units, analyzing their structure, meaning, and usage across different contexts. By drawing on examples from various languages, the research identifies common semantic features such as metaphor, irony, exaggeration, and synecdoche.
Keywords: phraseological toponyms; semantics; figurative language